1940
DOI: 10.1104/pp.15.3.409
|View full text |Cite
|
Sign up to set email alerts
|

The Balance Sheet of Metabolites For Potato Discs Showing the Effect of Salts and Dissolved Oxygen on Metabolism At 23° C1

Abstract: IntroductionThis paper presents a summarv of the effects of various salt and oxi-gen treatments so chosen that they comprise a range of conditions of peculiar interest to the student of salt accumulation.In any account of plant metabolism important processes may evade recognition unless a balance sheet of the principal metabolites can be prepared. Such balance sheets have rarely been attempted although the work of RAISTRICK et al. (31) on fungi is a notable exception. The work of RAISTRICK was concerned, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

1942
1942
1964
1964

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 14 publications
(19 reference statements)
4
18
0
Order By: Relevance
“…Calcium ion was found to exert a depressing effect upon these same activities. The extent of these phenomena are clearly seen in the data of Steward et al (24).…”
supporting
confidence: 68%
“…Calcium ion was found to exert a depressing effect upon these same activities. The extent of these phenomena are clearly seen in the data of Steward et al (24).…”
supporting
confidence: 68%
“…However, it seems not improbable that there is a metabolically' controlled system which accumulates water in a manner analogous to the way ions are accumulated. Indeed, suggestions of this sort, under the name of "active" water uptake, have been made by several authors (8,4; cf. also (3) It may be suggested that those metabolic processes which are intimately linked with growth are the same as those linked with aerobic water uptake.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we have mounted the potato discs so as to break the surface of a shallow unaerated solution. The apparatus consists of a fine net stretched over a large glass ring, 8 after six days has varied from 7 to 13%. Discs submerged in-the same volume of water, under a depth of about 5 mm., show less than half the water absorption.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of translocation in higher plants derived from sugar analyses of sap (10,26,27,28), aphid stylet exudates (24,28) and by the displacement of C14 from mature leaves (1,6,7,11,12,20,23), have produced the generally accepted view that sucrose is the main form of transported carbon in phloem tissue (19). These studies however have been confined to a very limited number of plant species.…”
Section: Introductionmentioning
confidence: 99%